2011 Proceedings IEEE INFOCOM 2011
DOI: 10.1109/infcom.2011.5934987
|View full text |Cite
|
Sign up to set email alerts
|

IMDGuard: Securing implantable medical devices with the external wearable guardian

Abstract: Abstract-Recent studies have revealed security vulnerabilities in implantable medical devices (IMDs). Security design for IMDs is complicated by the requirement that IMDs remain operable in an emergency when appropriate security credentials may be unavailable. In this paper, we introduce IMDGuard, a comprehensive security scheme for heart-related IMDs to fulfill this requirement. IMDGuard incorporates two techniques tailored to provide desirable protections for IMDs. One is an ECG based key establishment witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
198
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 209 publications
(202 citation statements)
references
References 14 publications
1
198
1
2
Order By: Relevance
“…A fair comparison between this and our other experiments -which employ a 20-FPS camera -requires that the individual IPI bits represent a similar frequency content. To this end, we first halve the IPI values obtained using our 50 FPS experiment prior to calculating the BER, effectively representing the BER values as-if they were obtained using a 25 FPS camera 6 . Note that the BER is considerably lower than when a 20 FPS camera is used, i.e., a higher camera-frame rate can increase the accuracy of rPPG.…”
Section: B Experimental Resultsmentioning
confidence: 99%
“…A fair comparison between this and our other experiments -which employ a 20-FPS camera -requires that the individual IPI bits represent a similar frequency content. To this end, we first halve the IPI values obtained using our 50 FPS experiment prior to calculating the BER, effectively representing the BER values as-if they were obtained using a 25 FPS camera 6 . Note that the BER is considerably lower than when a 20 FPS camera is used, i.e., a higher camera-frame rate can increase the accuracy of rPPG.…”
Section: B Experimental Resultsmentioning
confidence: 99%
“…To reduce battery consumption in IMDs, methods have been suggested that use an external device (called a cloaker) [17][18][19]. A cloaker is a device, such as a smartphone, that operates on behalf of the IMD.…”
Section: Communication Cloakingmentioning
confidence: 99%
“…Tippenhauer et al demonstrated that the shield does not provide confidentiality as a MIMO eavesdropper could cancel out the interference produced by the shield and then recover the messages sent by the devices [21]. Xu et al introduced a wearable device, also known as "IMDGuard", which does not only work as a proxy but also performs an authentication process on the ICD's behalf [22]. But Rostami et al found that the "IMDGuard" is vulnerable to a Man-InThe-Middle (MITM) attack which reduces its effective key length from 129 bits to 86 bits [19].…”
Section: Countermeasuresmentioning
confidence: 99%